1994
DOI: 10.1002/jcu.1870220603
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasonography of normal neck veins

Abstract: Doppler ultrasonography was used to examine 198 neck-vein systems (67 right, 131 left) in 148 patients. The vessel lumen is usually echo-free: the veins are supple, and the internal jugular and sometimes the subclavian veins can be compressed. The venous confluence is Y-shaped. Blood flow was symmetrical and biphasic in 57% of cases, continuous in 29% of cases, and monophasic in 13% of cases. Blood flow velocity was less than 1 m/s in all cases and varied with respiration and heart rate. Color Doppler allows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…The rare case of unilateral IJV agenesis, as in one of our patients, had been previously reported [18,19]. Pucheu et al [18] found in a group of 148 patients 3 cases of hypoplasia of variable degree of the left IJV with a diameter less than 0.5 cm and 1 case of complete agenesis of the left IJV.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The rare case of unilateral IJV agenesis, as in one of our patients, had been previously reported [18,19]. Pucheu et al [18] found in a group of 148 patients 3 cases of hypoplasia of variable degree of the left IJV with a diameter less than 0.5 cm and 1 case of complete agenesis of the left IJV.…”
Section: Discussionmentioning
confidence: 61%
“…Pucheu et al [18] found in a group of 148 patients 3 cases of hypoplasia of variable degree of the left IJV with a diameter less than 0.5 cm and 1 case of complete agenesis of the left IJV. In a US screening of children under the age of 6 years, the prevalence rate of agenesis of the internal jugular vein was 2 % [19].…”
Section: Discussionmentioning
confidence: 98%
“…Although there are anatomical variations, the valves are generally located about 0.5 cm above the union of the subclavian vein and IJVs at the lower limit of the jugular bulb [81-85], which are shown in 96.8% of the general population [82,84]. The IJV valves are generally thought to prevent the backflow of venous blood and backward venous pressure into the cerebral venous system during conditions where the central venous pressure or intrathoracic pressure is increased, such as chest compression during external cardiopulmonary resuscitation, severe or repetitive cough and straining [81,83-86].…”
Section: Anatomy Of the Extracranial Venous Systemmentioning
confidence: 99%
“…In early anatomic studies, the VV was not considered to be a relevant vessel, but instead as a venous plexus around the vertebral artery. In contrast to the IJVs, which have been the focus of anatomic and physiologic research since the first days of duplex sonography, 68, 69 up to now only one paper has been published reporting detection rates and flow velocities of 138 healthy subjects (mean age±s.d. 42.1±14.5 years) in supine position.…”
Section: Ultrasound Studiesmentioning
confidence: 99%